MULTIMATHEMACY: Anthropology and Mathematics Education - Pinxten, Rik (Springer International Publishing : Imprint: Springer, 2016)
This book aims at agents in education and social actions in every cultural environment. But it is also attractive to mathematicians, anthropologists and other specialists. It offers a broad and scholarly view of knowledge and culture and a very original transcultural and transdisciplinarian approach to education. Ubiratan D'Ambrosio, UNICAMP/Universidade Estadual de Campinas, Brazil.